El fenómeno de la migración interna y su impacto en la escolaridad - Ayala Ayala, Nelly Alejandrina (2017)
This project allows to know the current situation of many rural communities where migration is present, one of the main obvious threats caused by the need for higher income for home support. Therefore, the purpose came about as a response to a problem that affects all rural educational institutions of the country, particularly in the object of study institution, where the causes that carries this problem affect in the breakdown of the family and thus to society, thus parents leave children in the care of people nearby without taking into account the consequences resulting from this situation. The objective of this research was focused on diagnosing the phenomenon of internal migration and its impact on schooling of CECIB, Basic Education "Saraugsha", located in the Zumbahua, Pujili. Therefore, this project was carried out through the descriptive research, the same allowing collecting the necessary information for the theoretical foundation, the analysis and interpretation, using methods such as: analytical, synthetic and statistical with the use of techniques and instruments like the survey that was applied to educative community through the questionnaire. As a consequently, the results were evident allowing to know migration affects the academic and behavioral performance from students, so this has contributed to understand the attitudes and actions of them; contribute with solutions related to academic and family level in order to change this circumstance, the conclusions and recommendations as an outcome of it and thus improving the children progress with the whole community.